PENAKAR CURAH HUJAN AUTOMATIS MENGGUNAKAN MIKROKONTROLER ATMEGA 32 - Sumardi, Sumardi (Transmisi, 2009)
Indonesia is one kind of country which has wet tropical climate (humid tropic). The character has always high volume of rains. The average for each year in Indonesia isn’t in the same portion. But there still much more, an average 2000–3000 mm/year. And also between one and the other places have different rain rates. Areas which have rain rate less than 1000 mm, coverage of 0,6% from Indonesian territory, There are South east of Nusa, and 2 areas in Sulawesi (Palu valley and Luwuk). And some areas which have rain rates between 1000 – 2000 mm in a year there are some part of South east of Nusa, a little part of Merauke, Aru Archipelago and Tanibar. The areas which have rain rates between 2000 – 3000 mm per year, coverage East Sumatra, South Kalimantan, East part of West Java and Central Java, and some part of Irian Jaya, maluku Archipelago and some of Sulawesi. The area which has the most portion of rain 3000 mm per year is high land of West Sumatra, Central Kalimantan, and central plateau of Papua, more areas in Java, Bali, Lombok, and Sumba. Since this conditions, needed to improve a tools to detect total of rain rate prototype, so rain rate data in one place could be known quickly. This is so meanly to give advantage, for example to anticipate or warn from flood disaster or even landslide. In this research designed hardware to detect rain rate automatically using tipping bucket rain rate sensor. This sensor employed based on signal pulse caused of tipping moving from the rain which called click. Once click produce one pulse feed up to microcontroller to be recorded. Once click shows the number of flow rains 5,5 mm. Total flow rains recorded and accumulated from 06.00 until 17.00 and from 17.00 until 06.00. This result saved in its memory to an exact time suitable with memory capacity which still available in microcontroller. Keywords: rain rate detector, tipping bucket